2007
DOI: 10.1007/s11661-007-9230-6
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Zirconium on the Low-Cycle Fatigue Response of Ultrafine-Grained Copper

Abstract: This article reports on the influence of zirconium (Zr) addition (0.17 wt pct) on the cyclic stability of ultrafine-grained (UFG) oxygen-free high-conductivity (OFHC) copper (Cu) of originally high (99.995 wt pct) purity processed via equal-channel angular extrusion (ECAE). Systematic low-cycle fatigue (LCF) tests accompanied by microstructural investigation revealed that a Zr addition substantially affects the cyclic stability of UFG Cu, such that longer fatigue lives, notable cyclic hardening, and higher str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…30) As described in the chapter 2, the SUS430 steel involves Cr23C6 carbide particles 21) with the average particle spacing of ~2.1 μm and the average particle diameter of ~0.23 μm. However, the effect of Cr23C6 carbide particles on the generation of equiaxed submicron grains may be small in this steel, because the average particle spacing is much larger than the average length of ultra-fine equiaxed grains (~0.50 μm) and the volume fraction of the carbide particles is very small (smaller than 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…30) As described in the chapter 2, the SUS430 steel involves Cr23C6 carbide particles 21) with the average particle spacing of ~2.1 μm and the average particle diameter of ~0.23 μm. However, the effect of Cr23C6 carbide particles on the generation of equiaxed submicron grains may be small in this steel, because the average particle spacing is much larger than the average length of ultra-fine equiaxed grains (~0.50 μm) and the volume fraction of the carbide particles is very small (smaller than 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Another important parameter influencing the impact response is the texture of the material, and in particular, the distribution of grain boundary misorientation angles (GBMAs), which becomes of significant importance in UFG materials: High-angle grain boundaries hinder or slow down crack propagation by constituting even more effective barriers against dislocation motion, leading to improved fracture toughness and lower DBTT values. [24][25][26][27][28] In addition a)…”
Section: Introductionmentioning
confidence: 99%
“…38,40 However, it has been previously demonstrated that the GBMA distribution is also an important element of texture that strongly influences the deformation response especially in the case of UFG materials. [11][12][13][26][27][28]38,42 With this objective, the authors had previously developed an algorithm that constructs a three-dimensional grain neighborhood based on the two-dimensional experimental texture measurements 42 to incorporate the role of GBMA distribution into crystal plasticity. 38 The corresponding results had demonstrated that the incorporation of the GBMA distribution provided more accurate predictions not only for UFG microstructures, but also for CG materials, when predicting the deformation response.…”
mentioning
confidence: 99%
“…[1] An interesting observation is that, despite the success of the current formulations accounting for the texture in predicting the overall deformation response of the material, texture has been mostly incorporated either on a statistical basis or as a means of defining the orientation of grains in the matrix. [1] However, based on both experimental and theoretical evidence, one can argue that certain problems, especially the ones concerning dislocationgrain boundary interactions in ultrafine-grained (UFG) materials, [2][3][4][5][6][7][8][9][10][11][12][13] and lattice misorientations, [14][15][16][17][18] require a more detailed treatment of texture.…”
mentioning
confidence: 99%
“…[19,[20][21][22][23]24] It has been demonstrated that the misorientation of adjacent grains, and thus, the respective volume fractions of LAGBs and HAGBs, directly influence the deformation response and cyclic stability. [2][3][4][5] Specifically, HAGBs provide effective barriers against dynamic recrystallization and grain growth due to cyclic deformation, and thus, promote cyclic stability, such that dislocations stay anchored at HAGBs. However, LAGBs cannot resist the glide of mobile dislocations, and neighborhoods of grains with LAGBs easily become rearranged to yield larger grains with proceeding cyclic plastic deformation, threatening microstructural integrity and stability.…”
mentioning
confidence: 99%